International entrepreneurship: The pursuit of entrepreneurial opportunities across national borders - Reuber, A. Rebecca; Knight, Gary A.; Liesch, Peter W.; Zhou, Lianxi (Journal of International Business Studies, 2018)
In this editorial for the Special Issue on International Entrepreneurship, we inter-relate key concepts about the pursuit of opportunities from the entrepreneurship and international business literatures. In doing so, we consider the assessment of opportunities as an individual-level cognitive activity, the construction of opportunity as a firm-level innovative activity and the shaping of opportunity as an institutional-level structuring activity. We then extend the discussion to explore the notion of a distributed, global ecosystem of opportunities and opportunity seekers, which we believe may provide a platform for valuable future research.